Hubungan perilaku merokok dengan prestasi belajar siswa : The relationship between smoking behavior and student learning achievement - Beda, Nikodemus Sili; Komariah, Euis Dedeh; Palus, Gerardus Gusta; Badar, Petrus (Bali Medika Jurnal, 2021)
Smoking behavior is an activity to burn cigarettes and then smoke and blow them out and can cause smoke that can be inhaled by the people around them. In modern times, many people smoke, especially teenagers. A total of 28 (62.2%) class XII students at SMA PGRI 2 Makassar had poor smoking behavior and 17 (37.8%) grade XII students at SMA PGRI 2 Makassar had good smoking behavior. The purpose of this study was to determine the relationship between smoking behavior and student achievement of class XII at SMA PGRI 2 Makassar.This type of research is analytic observational with cross sectional approach. The study population was all students of class XII at SMA PGRI 2 Makassar. The sampling technique used was nonprobability sampling with a purposive sampling approach, with a total sample size of 45 people. Collecting data using a questionnaire for smoking behavior while learning achievement used documentation taken from the academic section. The statistical test used was the Chi-Squar test with Kolmogorov's alternative test. -smimov So that the value of Zhitung = 1.640> Ztabel = 0.198 supported by the value of p = 0.009 <0.05. These two things indicate that the count x2> x2 table and p value <α. From the two things mentioned above, it can be concluded that the null hypothesis (Ho) is rejected and Ha is accepted, meaning that there is a relationship between smoking behavior and learning achievement. So it can be concluded that in cigarettes there are chemical substances such as nicotine which can inhibit intelligence, proficiency level, reduce enthusiasm for learning, and reduce learning concentration.